Incidencia de la aplicación del sistema de las detracciones a la primera venta de inmuebles en la recaudación en la provincia de Trujillo - Meza Rosas, Carlos Samuel (2016)
By the present investigation seeks to determine if it was positive the impact of the application of the system of withdrawals after the first sale of properties in the collection in the province of Trujillo. In order to achieve the objective of this thesis, in the framework of the system is defined withdrawals from your application with the Legislative Decree No. 940 in 2001 in a much broader context, then go into more detail the recent implementation of the withdrawals system to the first sale of property, taking into account that although an assumption that was already contemplated the Legislative Decree, the procedure was regulated by the Tax Administration Superintendency Resolution 022-2013 SUNAT force from the first of February 2013, pursuant to the determination of indicators of continued tax noncompliance by the builders of these real estate projects nationwide. Finally, this research aims to contribute to the discussion and analysis to detail the application of the system of transfers to the first sale of properties in the collection in the province of Trujillo, as the construction sector quite significant in national economic growth . Considered necessary to take into account the opinion from a representative of the Tax Administration and that was why I was able to interview the current Regional Intendant of La Libertad Dr. Patricia G. Silva in order to have a more accurate idea of the implications of the application of the system of withdrawals in the region, taking into account the different views of the direct participants in the application of the rule in question